Phylogenetic relationships and systematic position of the families Cortrematidae and Phaneropsolidae (Platyhelminthes: Digenea) - Kanarek, Gerard; Zaleśny, Grzegorz; Sitko, Jiljí; Tkach, Vasyl V (Folia parasitologica, 2014)
The systematic position and phylogenetic relationships of the family Cortrematidae Yamaguti, 1958 have always been controversial. In the present study, the phylogenetic relationships of this family and its constituent genera and families within the superfamily Microphalloidea were evaluated using previously published and newly obtained sequences of 28S rDNA of Cortrema magnicaudata (Bykhovskaya-Pavlovskaya, 1950) (Cortrematidae), Phaneropsolus praomydis Baer, 1971 and Microtrema barusi Sitko, 2013 (Phaneropsolidae). Results clearly demonstrate that the genus Cortrema Tang, 1951 is closest to Gyrabascus Macy 1935, both genera forming one of the clades within the family Pleurogenidae in the superfamily Microphalloidea and sharing several important morphological features. Thus, the family Cortrematidae should be considered among synonyms of the Pleurogenidae. Based on the analysis of morphology, C. corti Tang, 1951, C. testilobata (Bykhovskaya-Pavlovskaya, 1953) and C. niloticus Ashour, Ahmed et Lewis, 1994 are considered junior synonyms of C. magnicaudata. The phylogenetic position of P. praomydis as a family-level branch not showing close relationships with other families of the Microphalloidea, supports the status of the Phaneropsolidae as an independent family. The genus Parabascus Looss, 1907 previously considered within the Phaneropsolidae clearly belongs to the Pleurogenidae. In addition, the molecular phylogeny has demonstrated that the recently described phaneropsolid Microtrema barusi belongs to the microphallid genus Microphallus Ward, 1901. Therefore, Microtrema Sitko, 2013 is considered a junior synonym of Microphallus. Our analysis has also confirmed the status of Collyriclidae as a family within the Microphalloidea. Not yet sequenced representatives of other families within the Microphalloidea (e.g. Anenterotrematidae, Eumegacetidae, Renschtrematidae, Stomylotrematidae, etc.) need to be included in future molecular phylogenetic studies to better unravel the taxonomic structure and content of this diverse digenean superfamily.
Keywords: Animals; DNA, Helminth; ploštěnci; Phylogeny; Platyhelminths; zvířata; DNA helmintů; fylogeneze